The business of choice : how human instinct influences everyone's decisions - Willcox, Matthew (Emerald Publishing Limited, 2020)
In this 2nd edition of The Business of Choice, expert author and consultant Matthew Willcox explores the science of influencing choice, bringing together the work of thousands of behavioral scientists and practitioners. Cutting to the heart of the science, Willcox helps you apply this to your own marketing and brand strategies.